Agrobacterium Biology From Basic Science to Biotechnology (Current Topics in Microbiology and Immunology,, 2018)
This volume reviews various facets of Agrobacterium biology, from modern aspects of taxonomy and bacterial ecology to pathogenesis, bacterial cell biology, plant and fungal transformation, natural transgenics, and biotechnology. Agrobacterium-mediated transformation is the most extensively utilized platform for generating transgenic plants, but modern biotechnology applications derive from more than 40 years of intensive basic scientific research. Many of the biological principles established by this research have served as models for other bacteria, including human and animal pathogens. Written by leading experts and highlighting recent advances, this volume serves both as an introduction to Agrobacterium biology for students as well as a more comprehensive text for research scientists.